IP3 receptor isoforms differently regulate ER-mitochondrial contacts and local calcium transfer - Adam Bartok (Nature Portfolio, 2019)
Membrane contact sites between the ER and mitochondria are known to convey calcium signals between these two organelles via IP3 receptors, but the molecular mechanisms are currently unclear. Here, the authors show that IP3 receptors play a structural tethering role in maintaining ER-mitochondrial contacts.